ABC's of relationship selling through service - Futrell, Charles M. (McGraw-Hill, 2007)
"ABC's of Relationship Selling, 9/E" by Futrell is written by a sales person turned teacher and is filled with practical tips and business-examples gleaned from years of experience in sales with Colgate, Upjohn, and Ayerst and from the author's sales consulting business. Charles Futrell focuses on improving communication skills and emphasizes that no matter what career a student pursues, selling skills are a valuable asset. This text contains a wealth of exercises and role plays. The text also makes a nice companion to a sales management text in Marketing programs that offer a sales management course, but do not offer a separate selling course. --This text refers to an out of print or unavailable edition of this title.